Astrocytic modulation of excitatory synaptic signaling in a mouse model of Rett syndrome - Benjamin Rakela; Paul Brehm; Gail Mandel (eLife, 2018)
Studies linking mutations in Methyl CpG Binding Protein 2 (MeCP2) to physiological defects in the neurological disease, Rett syndrome, have focused largely upon neuronal dysfunction despite MeCP2 ubiquitous expression. Here we explore roles for astrocytes in neuronal network function using cortical slice recordings. We find that astrocyte stimulation in wild-type mice increases excitatory synaptic activity that is absent in male mice lacking MeCP2 globally. To determine the cellular basis of the defect, we exploit a female mouse model for Rett syndrome that expresses wild-type MeCP2-GFP in a mosaic distribution throughout the brain, allowing us to test all combinations of wild-type and mutant cells. We find that the defect is dependent upon MeCP2 expression status in the astrocytes and not in the neurons. Our findings highlight a new role for astrocytes in regulation of excitatory synaptic signaling and in the neurological defects associated with Rett syndrome.